A Critical Study on Identity In the Novels of Jhumpa Lahiri: Exploring the Challenges of Identity in Jhumpa Lahiri's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Question of identity is always a difficult one, andespecially for those who are culturally displaced. The immigrants are those whogrow up in two worlds. Jhumpa Lahiri believes that for immigrants, thechallenge of exile, the loneliness, the constant sense of alienations, the knowledgeof and longing for a lost world are more explicit and distressing than fortheir children. The Namesake is essentially, a story about the struggles andhardships of a Bengali couple who immigrate to the United States to form a lifeoutside of everything they know.